1995
DOI: 10.1006/cbir.1995.1061
|View full text |Cite
|
Sign up to set email alerts
|

Glycolipid patterns during xenopus embryo development

Abstract: Glycolipid patterns have been studied during the first six days of Xenopus embryo development. Glycolipid contents showed a sharp increase more evident after the third day of development. Glucosylceramide and sulphatide are not only the most represented species, but also those which exhibit a statistically significant percentage change during early development. Among gangliosides, GD3 is the most represented specie. Two polysialylated gangliosides with not yet established structures are also present.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
4
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 10 publications
4
4
0
Order By: Relevance
“…Up-regulation of oligosialylation along zebrafish development is in agreement with previous observations made on Xenopus laevis showing by in vitro assays that ST8Sia I (SAT-2) and ST8Sia V (SAT-4) activities were dramatically increased along the early development, with a maximum activity at day 4 [47]. However, whereas quantities of both neutral glycolipids and gangliosides sharply increase in X. laevis, only gangliosides appear to be up-regulated in D. rerio [48]. In contrast to glycolipids, evolution of glycoproteins associated α2,8-sialylation does not correlate with the temporal expression and the general increase of mRNAs of ST8Sia II, ST8Sia IV and ST8Sia VI from 10 hpf along the early stages of zebrafish development, therefore implicating a different kind of regulation.…”
Section: Discussionsupporting
confidence: 92%
“…Up-regulation of oligosialylation along zebrafish development is in agreement with previous observations made on Xenopus laevis showing by in vitro assays that ST8Sia I (SAT-2) and ST8Sia V (SAT-4) activities were dramatically increased along the early development, with a maximum activity at day 4 [47]. However, whereas quantities of both neutral glycolipids and gangliosides sharply increase in X. laevis, only gangliosides appear to be up-regulated in D. rerio [48]. In contrast to glycolipids, evolution of glycoproteins associated α2,8-sialylation does not correlate with the temporal expression and the general increase of mRNAs of ST8Sia II, ST8Sia IV and ST8Sia VI from 10 hpf along the early stages of zebrafish development, therefore implicating a different kind of regulation.…”
Section: Discussionsupporting
confidence: 92%
“…Our results are in keeping with the ones reported by Gornati et al (1995Gornati et al ( , 1997 concerning the in vitro activities of sialidases and glycosyltransferases during the early development of X. laevis. They found that GD3 was the most represented ganglioside during early embryogenesis and that SAT-2 (GD 3 synthase) had an activity peak at day 4 of development (Gornati et al, 1997).…”
Section: Xlcgt and Xlgd 3 Synthase Temporal And Spatial Expression Pasupporting
confidence: 94%
“…The activities of glycosyltransferases and sialidases during the early development of Xenopus, analyzed by Gornati et al (1995Gornati et al ( ,1997, showed the highest enzymatic activity during early embryogenesis. Recently, Rimoldi et al (2007) reported the sequences of two another isoforms of ST8Sia I and their expression during later Xenopus embryogenesis, probably reflecting the pseudotetraploidy in Xenopus laevis.…”
Section: Introductionmentioning
confidence: 99%
“…There is increasing evidence that GSL and especially gangliosides are expressed during amphibian development and may be involved in the cellular events that take place during development (Turner et al, 1992;Gornati et al, 1995;Kubo et al, 1995). In 1974, Stearns suggested that yolk platelets provide the organic components used during segmentation and in cell-cell recognition during gastrulation (Stearns, 1974).…”
Section: Discussionmentioning
confidence: 99%
“…In 1991, Hidari et al determined the composition of acidic glycolipids in the oocyte of the amphibian Xenopus. More recently, Gornati et al (1995) established the pattern of both neutral glycosphingolipids and gangliosides during the first 6 days of Xenopus laevis development. Moreover, a neutral glycolipid was found to be involved in a novel cellular adhesion mechanism.…”
Section: Introductionmentioning
confidence: 99%